Investigations into the presence of functional ß1, ß2 and ß3-adrenoceptors in urothelium and detrusor of human bladder - Pradeep Tyagi (International Brazilian Journal of Urology, 2009)
Purpose: We investigated the presence of functional ß1, ß2 and ß3-adrenoceptor in urothelium and detrusor muscle of human bladder through in vitro pharmacology of selective ß3 adrenoceptor agonist solabegron. Materials and Methods: Expression of these adrenoceptors in surgically separated human urothelium and detrusor muscle were investigated using RT-PCR. The effects of activating these receptors were studied by determining the relaxation produced by ß-adrenoceptors agonist in pre-contracted human detrusor strips. Results: The results confirmed the presence of mRNA for ß1, ß2 and ß3-adrenoceptor in both human urothelium and detrusor. In an in vitro functional bladder assay, Solabegron and other agonists for ß-adrenoceptors such as procaterol and isoproterenol evoked potent concentration-dependent relaxation of isolated human bladder strips with pD2 values of 8.73 ± 0.19, 5.08 ± 0.48 and 6.28 ± 0.54, respectively. Conclusions: Selective ß3-adrenoceptor agonist may be a potential new treatment for the overactive bladder OAB syndrome. Existence of ß3-adrenoceptor mRNA exists in the urothelium in addition to the detrusor muscle suggest multiple site of actions for the ß3-adrenoceptor in the lower urinary tract.